KEGIATAN MENYANYI “BERHITUNG SEDERHANA” UNTUK MENUMBUH-KEMBANGKAN NUMERICAL SELF-EFFICACY SISWA PRA-SEKOLAH TK TEGAL BEDUG, INDRAMAYU, JAWA BARAT - Dariyo, Agoes; Andrianputra, Ezra (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
Tegal Bedug Kindergarten students experience problems related to academic self-efficacy, especially simple arithmetic. They feel less confident about arithmetic lessons which also impacts on their lack of confidence in their future lives in society. They are the young generation who need serious attention from adults, especially Kindergarten teachers. This activity is a singing activity